Health utility values for patients with recurrent acute rhinosinusitis undergoing endoscopic sinus surgery: a nested case control study. Issue 11 (16th June 2016) - Steele, Toby O.; Mace, Jess C.; Dedhia, Raj; Rudmik, Luke; Smith, Timothy L.; Alt, Jeremiah A.
Abstract : Background: Health utility scores quantify an individual's valuation of particular health states and are vital components of health economic studies and cost‐effectiveness research. We sought to characterize health utility values for patients with recurrent acute rhinosinusitis (RARS) both before and after endoscopic sinus surgery (ESS), as well as compare health utility to chronic rhinosinusitis without nasal polyposis (CRSsNP). Methods: Patients with RARS (n = 20) and CRSsNP (n = 20) undergoing ESS were enrolled as part of a longitudinal, observational, prospective cohort. Case patients diagnosed with RARS were age‐ and gender‐matched to controls with CRSsNP using a nested case‐control design at a 1:1 ratio. Health utility was measured using the Medical Outcomes Study Short Form‐6D (SF‐6D) survey. Results: Patients with RARS were followed for an average of 14.0 ± 6.1 (mean ± standard deviation) months compared to an average of 14.4 ± 5.3 months for CRSsNP controls ( p = 0.779). Mean preoperative SF‐6D health utility scores were statistically comparable between RARS (0.71 ± 0.14) and CRSsNP (0.66 ± 0.12; p = 0.341). Both patients with RARS and CRSsNP reported significant postoperative improvement in SF‐6D scores from 0.71 ± 0.14 to 0.79 ± 0.13 ( p = 0.031) and from 0.66 ± 0.12 to 0.77 ± 0.13 ( p = 0.004), respectively. No difference in last postoperative SF‐6D scores were found between RARS and CRSsNP ( p = 0.583) or in the average magnitude of postoperative improvement (0.08 ± 0.16 vs 0.11 ± 0.13; p = 0.620). Conclusion: Patients with RARS and CRSsNP report significant impairment in health utility as measured by the SF‐6D. ESS significantly improves health utility in patients with RARS and CRSsNP to near normative values. These data will help inform future economic analysis and cost‐effectiveness research.